Effects of colchicine on polyploid induction, morphology, and yield components of several Thai rice varieties - SUNTAREE SURSON; SUPHASIT SITTHAPHANIT; JAKKAPAT PRACHACHIT; THARADOL JITJAK; KHUMPANAT WONGKERSON (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Surson S, Sitthaphanti S, Prachachit J, Jitjak T, Wongkerson K. 2024. Effects of colchicine on polyploid induction, morphology, and yield components of several Thai rice varieties. Biodiversitas 25: 4677-4689. Rice (Oryza sativa) is a Thai staple food and is different from foreign rice in its characteristics. By producing polyploids, rice cultivation becomes resistant to unfavorable climatic conditions and produces good yields and good tastes. Inducing polyploidy can improve Thai rice. This research aimed to induce polyploid formation in Thai rice to be used as a breeding source for improving Thai polyploid rice in the future. This study created polyploids from 10 Thai rice varieties to test colchicine's impact on morphology and yield. Colchicine-treated rice plants were tested for polyploidy at 4 months of age using flow cytometry and awn seed characteristics. The results showed that colchicine treatment and varied exposure periods at 1 month of age significantly affected germination and abnormalities in rice varieties. Variations in rice varieties and exposure times resulted in varying morphological and yield component attributes at 3 months. All colchicine-treated rice types had 5-90% awn seeds. This study reveals that rice varieties and exposure durations affect the morphology and features of yield components. Awn seeds determined rice polyploidy, which varied by variety. Blackberry has the most awn-seed plants (90%), followed by Maejo 2 (60%), and Homnaka (60%).